UPAYA KEMENTERIAN PERDAGANGAN DALAM MELINDUNGI USAHA MIKRO KECIL DAN MENENGAH DARI PRAKTIK PREDATORY PRICING - Siti Shabrina Cesariana (2023)
The practice of predatory pricing is one of the business competition strategies that is often applied by business actors. This practice is included in unfair business competition which is often used by large and dominant companies to get rid of their competitors and prevent other business actors who have the potential to become competitors from entering the same market. This study aims to find out how the impact of predatory pricing practices has on the sustainability of micro, small and medium enterprises and also how the efforts of the Ministry of Trade protect micro, small and medium enterprises from predatory pricing practices, especially those that occur in e-commerce. The research was carried out using normative juridical methods by examining laws and regulations related to the legal issues to be studied. From this study it was found that predatory pricing practices have a negative impact on the sustainability of micro, small and medium enterprises (MSMEs) which also have a negative impact on the country's economy. The government, through the Ministry of Trade, is collaborating with the Ministry of Cooperatives and SMEs to try to change the regulations regarding predatory pricing in e-commerce in the Minister of Trade Regulation Number 50 of 2020 concerning Provisions for Business Licensing, Advertising, Guidance and Supervision of Business Actors in Trading Through Electronic Systems (PMSE) because it can threaten local MSME products.